MCQs in Pharmaceutical Science and Technology - Garg, Sanjay (London, United Kingdom : Pharmaceutical Press, 2011)
Designed as a study aid, this resource is compreised of 300 MCQs and answers in pharmaceutical science. Questions included in each chapter cover the basic, conventional and novel delivery systems and allows students to gain much needed practice in this discipline.
Physical pharmaceutics -- Pharmacokinetics and biopharmaceutics -- Particle science and calculations -- Dosage from design -- Advanced drug-delivery systems -- Miscellaneous topics
Includes index.
Keywords: PHARMACEUTICAL EXAMINATIONS, QUESTION, ETC